Pembentukan Pemikiran Kreatif dan Kritis: Hubungannya Dalam Menyelesaikan Masalah - Anita Ismail; Adibah Sulaiman; Mashitah Sulaiman; Farah Laili Muda @Ismail; Mohd Azmir Mohd Nizah; Latifah Abdul Latiff; Siti Norbaya Mat Yaacob; Hisham Mohammad Taky Eldin Kandil (USIM Press, 2024)
Vol. 5 No. 1 (2020): Jurnal Sains Insani